Fructan Catabolism by Rumen Microbiota of Cattle and Sheep - Jennifer R. Weinert-Nelson; Isabelle A. Kagan; Donald G. Ely; Michael D. Flythe; Brittany E. Davis (Fermentation, 2023)
Fructans serve as the primary form of storage carbohydrate in cool-season grasses, but little is known about potential differences in ruminal fermentation of fructans between cattle and sheep. An ex vivo study was conducted to evaluate species differences in fructan catabolism. Buffered media containing ground orchardgrass (Dactylis glomerata L.) substrate was inoculated with uncultivated rumen microbiota obtained from cattle and sheep (n = 4 species−1). Fructan profiles were monitored over the incubation period (8 h; 39 °C) using high-performance anion-exchange chromatography coupled to pulsed amperometric detection (HPAEC-PAD). In both species, disappearance of long-chain fructans (degree of polymerization [DP] > 8) was evident by 2 h of incubation (p < 0.01), whereas short-chain fructans (DP 4–8) increased from 0 to 2 h prior to subsequent degradation (p < 0.01). However, the overall rate of long-chain fructan catabolism was greater in bovine versus ovine fermentations, particularly between 2 and 4 h (p < 0.01). Additionally, rapid utilization of short-chain fructans occurred from 2 to 4 h in bovine fermentations, but was delayed in ovine fermentations, with substantial degradation occurring only after 4 h of incubation (p < 0.01). These results indicate that rumen microbiota of cattle may have a greater capacity for fructan degradation.